Creative Tourism: A Guide for Practitioners – How do you Regenerate Communities and Places by Combining Culture, Tourism and Creativity? - Vinagre de Castro, Tiago (2022)
How do you regenerate communities and places by combining culture, tourism and creativity? This booklet is intended to provide clarification and guidance to practitioners in the cultural, creative and tourism sectors currently developing or wishing to develop creative tourism projects based on collaborative practices, particularly in rural areas and small cities.